(3GdSLd GdhGQO Edi CHj fUQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUd cJGH SjOi GdTjN GdaGVd hhbaJ Ydi LejYg hMeOJ Gdgd Ydi ceGd SdGeJg hCeG eG PcQJg ef GMhGd GdMUU heSGQYI ef SGQY Edi s
(3BNQgG (B:s
(3adG JLYd Ydi bdHc KbdkG ef CeQ GHf eYdG adGHO jHdZc eG jMd Hg hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3abg GdePGgH GdCNQis